Potential barriers in implementing the rural toilet retrofitting project: A qualitative study in Jiaozuo, China - Wang, Yuan; Zhu, Yueqi; Qi, Caiyun; Li, Lu (Frontiers in Public Health, 2022)
Background: China has launched a large “toilet revolution” in rural areas, but the results show that sanitation has not always been markedly improved. Few scholars have paid attention to this issue, and the list of the reasons is scattered and incomplete. Method: Using the qualitative research method, this study interviewed seven village cadres and 39 villagers in three villages of Jiaozuo City to examine the implementation barriers to rural toilet retrofitting (RTR) projects in China. Results: Using the Van Meter and Van Horn policy implementation approach, the research has found that: (a) unreasonable standards and objectives fail to incorporate local conditions and improve the actual quality; (b) lack of capital and human resources cannot renovate new toilets; (c) uncoordinated inter-organizational communication and enforcement activities by top-down mechanism lead to policy implementers and target groups’ dissatisfaction with the policy; (d) weak and unenthusiastic, inadequate implementing agencies, reduce their working ability; (e) inappropriate economic, social and political conditions impede the villagers’ acceptance; and (f) an attitude of passive acceptance by the implementers reduce the working motivation. Conclusion: To improve sanitation in rural China, it is necessary to solve the six barriers. The findings of this study can provide recommendations and guidance for implementing the RTR and related public health policies.